Dissecting the role of Engrailed in adult dopaminergic neurons – Insights into Parkinson disease pathogenesis. Issue 24 (13th October 2015) - Rekaik, Hocine; Blaudin de Thé, François-Xavier; Prochiantz, Alain; Fuchs, Julia; Joshi, Rajiv L.
Abstract : The homeoprotein Engrailed (Engrailed‐1/Engrailed‐2, collectively En1/2) is not only a survival factor for mesencephalic dopaminergic (mDA) neurons during development, but continues to exert neuroprotective and physiological functions in adult mDA neurons. Loss of one En1 allele in the mouse leads to progressive demise of mDA neurons in the ventral midbrain starting from 6 weeks of age. These mice also develop Parkinson disease‐like motor and non‐motor symptoms. The characterization of En1 heterozygous mice have revealed striking parallels to central mechanisms of Parkinson disease pathogenesis, mainly related to mitochondrial dysfunction and retrograde degeneration. Thanks to the ability of homeoproteins to transduce cells, En1/2 proteins have also been used to protect mDA neurons in various experimental models of Parkinson disease. This neuroprotection is partly linked to the ability of En1/2 to regulate the translation of certain nuclear‐encoded mitochondrial mRNAs for complex I subunits. Other transcription factors that govern mDA neuron development (e.g. Foxa1/2, Lmx1a/b, Nurr1, Otx2, Pitx3) also continue to function for the survival and maintenance of mDA neurons in the adult and act through partially overlapping but also diverse mechanisms.